2017
DOI: 10.1038/ijo.2017.195
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and genomic adaptations to winter fattening in a primate species, the grey mouse lemur (Microcebus murinus)

Abstract: Altogether, these results show that mouse lemurs undergo deep physiological and genomic seasonal changes, without ever reaching a pathological stage. Further investigation is needed to decipher the underlying mechanisms, which may well be highly relevant for human therapeutic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
54
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(69 citation statements)
references
References 48 publications
10
54
5
Order By: Relevance
“…Thus, exposure to contrasting environmental conditions, leading to the expression of seasonal phenotypes may, in fact, help maintain a healthy dwarf lemur population in captivity, if hibernation is expressed in moderation 54 . A “renaturalized” captive dwarf lemur population will set the stage for future investigations of the mechanisms underlying hibernation expression and its regulation, for example exploring protective mechanisms that allow dwarf lemurs to tolerate spikes in sugar or lipid metabolism without showing signs of illness 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, exposure to contrasting environmental conditions, leading to the expression of seasonal phenotypes may, in fact, help maintain a healthy dwarf lemur population in captivity, if hibernation is expressed in moderation 54 . A “renaturalized” captive dwarf lemur population will set the stage for future investigations of the mechanisms underlying hibernation expression and its regulation, for example exploring protective mechanisms that allow dwarf lemurs to tolerate spikes in sugar or lipid metabolism without showing signs of illness 20 .…”
Section: Discussionmentioning
confidence: 99%
“…All individuals from this population were monitored from birth to death and provided with ad libitum water and shelter availability. Food was delivered in quantities that were sufficiently high to maximize reproduction and survival, while not too abundant to prevent excessive fattening and the negative consequences of long‐term obesity (Terrien et al, ). We hypothesize that under such conditions, with nonlimiting resources and virtually no extrinsic mortality, reproducing would not negatively affect future survival.…”
Section: Introductionmentioning
confidence: 99%
“…However, arousal from a hypometabolic state may generate a brief but massive peak in oxidative damage (Figure 1). In mouse lemurs, when metabolic activity increases, DNA oxidative damage increases and relative telomere length decreases (Terrien et al, 2017). Telomere shortening during this seasonal transition may be an adaptive response.…”
Section: Oxidative Stress and Genomic Instabilitymentioning
confidence: 99%
“…Recent work on the mouse lemur has shown that the relative expression of phospho-IRS-1 was enhanced in muscle during torpor but decreased in white adipose tissue, thus suggesting an inhibition of insulin/IGF-1 signaling during torpor in these tissues (Tessier et al, 2015). In parallel, animals seem to be protected from an inflammatory response during massive fattening (Terrien et al, 2017). Further work is needed to determine to what extent the mechanisms that prevent insulin resistance and inflammation during fattening are altered with age.…”
Section: Excess Fat and The Associated Inflammatory Responsementioning
confidence: 99%
See 1 more Smart Citation